Engineering Escherichia coli biofilm to increase contact surface for shikimate and L-malate production - Qiang Ding (SpringerOpen, 2021)
Abstract Microbial organelles are a promising model to promote cellular functions for the production of high-value chemicals. However, the concentrations of enzymes and nanoparticles are limited by the contact surface in single Escherichia coli cells. Herein, the definition of contact surface is to improve the amylase and CdS nanoparticles concentration for enhancing the substrate starch and cofactor NADH utilization. In this study, two biofilm-based strategies were developed to improve the contact surface for the production of shikimate and L-malate. First, the contact surface of E. coli was improved by amylase self-assembly with a blue light-inducible biofilm-based SpyTag/SpyCatcher system. This system increased the glucose concentration by 20.7% and the starch-based shikimate titer to 50.96 g L−1, which showed the highest titer with starch as substrate. Then, the contact surface of E. coli was improved using a biofilm-based CdS-biohybrid system by light-driven system, which improved the NADH concentration by 83.3% and increased the NADH-dependent L-malate titer to 45.93 g L−1. Thus, the biofilm-based strategies can regulate cellular functions to increase the efficiency of microbial cell factories based on the optogenetics, light-driven, and metabolic engineering. Graphical Abstract